(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Ayurveda a deeply human form of science, rooted in real-life outcomes obtained through extensive experimentation and research on all aspects that affect life. It offers insight into the intricate composition and functioning of human body (Shareera). The concept of Shadangatvam delves into the six main regions of body, while the Pratyangas provide further breakdowns of these regions. When exploring the Pratyangas, certain structures such as Srotas, Peshi and Ashayas the anatomical structures and physiological concepts will differ between genders. There are even discrepancies in numbers and structures. Peshi Sankhya varies according to gender. Peshi the building blocks of the human body originate from the Mamsa dhatu. They enclose the body like a sleeve, enveloping the Sira, Snayu, Asthi, and Sandhi by protecting and supporting these structures. Muscle tissue is a group of muscle fibers interconnected by connective tissue. They produce force and facilitate movement, regulating the body’s internal environment. By directing the working of these muscles, the human mind ultimately manifests itself. The muscular system plays a key role in enabling the movement of the human body. This information about Peshi arouses curiosity about their anatomical structure described in ancient texts. This study examines the information and logically analyses and interprets it in order to determine the probable accurate anatomical structures.